Comparison of the fractal dimension among swimmers with different levels of expertise - Barbosa, Tiago M. (2016)
It is known that performance is strongly related to proportional changes in the inputs. The “marginal gains theory” in sports performance gained popularity a few years ago. It encompasses the assumption that small changes in the input (or the sum of several changes) may have a significant effect on the output.